The Voice of the Voiceless in Munshi Premchand’s Karmabhumi: Unearthing the Struggles and Silenced Narratives in Munshi Premchand's Karmabhumi (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The prolific writer Munshi Premchand seems to be the most vocal voice of the voiceless, reason being he himself had been a victim of the so called imperial structures of the society ever since his formative years. The base behind this victimization lies in the fact that the age of Premchand was divided into different social structures. If anybody wanted to exist in that society, he had to accept it whole heartedly. But, Premchand, being the whistle-blower of the voiceless sections of the society, was the only person who resigned from his job for writing against those autocratic tendencies of the cross sectional society of the post-colonial India. His own experience of subordination process led him to understand the pain of the voiceless from multiple angles, such as social, economic, political, psychological and religious and gave vent to these aspects of subordination in his fictional works. Premchand has tried his best to project the deprivation of the voiceless sections of the colonial India, not by the colonizers but by feudal India itself. He recasts the fresh originality of the subalterns exposing pretensions and complacencies of dominant, feudal and traditional mores.